SOSIALISASI PERAN REKAM MEDIS ELEKTRONIK (RME) DALAM MENINGKATKAN EFISIENSI PELAYANAN DAN PELAPORAN DATA KESEHATAN DI UPT PUSKESMAS TEGAL SARI TAHUN 2025 - Br Sinulingga, Emmenita Carina (Jurnal Pengabdian Masyarakat Putri Hijau, 2026)
Electronic Medical Records (RME) is a digital-based patient data recording system that aims to increase the efficiency of health services and simplify the management and reporting of health data. However, in practice there are still health workers at community health centers who do not fully understand the role and optimal use of Electronic Medical Records (RME). Therefore, this Community Service (PKM) activity was carried out in the form of socialization regarding the role of Electronic Medical Records (RME) in improving the efficiency of health services and reporting at the Tegal Sari Community Health Center UPT in 2025. This activity aims to increase the knowledge and understanding of health workers at the Tegal Sari Community Health Center UPT regarding the importance of implementing electronic medical records in the patient care process. The methods used in this activity include delivering material, discussions and questions and answers, as well as simulations regarding the use of electronic medical records. The results of the activity showed that activity participants gained increased understanding regarding the use of electronic medical records in improving the efficiency of health services and reporting. With this activity, it is hoped that Health workers at the Tegal Sari Community Health Center UPT can make more optimal use of electronic medical records so that the quality of Health services and Health data management can improve.